Proapoptotic properties of total phytohemagglutinine and its individual isolectins in human cell culture 4BL - T. O. Kochubei; O. V. Maksymchuk; L. L. Маcewicz; О. O. Piven; L. L. Lukash (The Ukrainian Biochemical Journal, 2014)
Phytohemagglutinine (PHA) is widely investigated lectin with mitogenic properties. Recently it was shown that PHA is not only cell proliferation inducer, but also has a toxic or cytostatic effect. However concentration dependence and molecular mechanisms of this effect are not enough investigated. To study proapoptotic properties of total phytohemagglutinine and its isolectins in human cell culture of not tumor origin 4BL we observed a change in the frequency of apoptotic cells in the tested cell culture under the influence of the total phytohemagglutinine and erythroagglutinin by the method of specific color luminescent dye. The activation of caspases-3 and -8 and induction of protein Bax expression under the influence of lectins were detected by Western blot analysis. It was revealed that erythroagglutinin induced apoptosis with the highest efficiency compared with leukoagglutinin and total phytohemagglutinine. The induction of apoptosis in human cell culture of not tumor origin 4BL is probably caused by activating caspase-dependent and mitochondrial signalling.